Modelling allosteric signalling in protein homodimers - Rodgers, Thomas; Burnell, David; Wilson, Mark R.; Pohl, Ehmke; Cann, Martin; Townsend, Philip D.; McLeish, Tom C.B.; Toncrova, Hedvika (2011)
Allostery in protein systems is a thermodynamic phenomenon. Allosteric response is driven by the free energy differences obtained in different binding events, which, in principle, contain contributions from both enthalpic and entropic changes. While traditional views of allostery have concentrated on structural changes induced by the binding of ligands (i.e. ‘‘enthalpically dominated’’), it is now increasingly recognised that fluctuations in structure can contribute to allosteric regulation. In some cases, where ligand-induced structural changes are small, thermal fluctuations can play a dominant role in determining allosteric signalling. In thermodynamic terms, the entropy change for subsequent binding is influenced by global vibrational modes being either damped or activated by an initial binding event. One advantage of such a mechanism is the possibility for long range allosteric signalling. Here, changes to slow internal motion can be harnessed to provide signalling across long distances. This paper considers homotropic allostery in homodimeric proteins, and presents results from a theoretical approach designed to understand the mechanisms responsible for both cooperativity and anticooperativity. Theoretical results are presented for the binding of cAMP to the catabolite activator protein (CAP) [1], where it is shown that coupling strength within a dimer is of key importance in determining the nature of the allosteric response. Results from theory are presented along side both atomistic simulations and simple coarse-grained models, designed to show how fluctuations can play a key role in allosteric signalling in homodimeric proteins.
EPrint Processing Status: Author unable to supply full text
Keywords: Centre for Humanities Engaging Science and Society; Durham Centre for Soft Matter; Centre for Materials Physics